Cervicometría por ecografía transvaginal como predictor de parto pretérmino en gestantes con amenaza de parto pretérmino en el Hospital Minsa II - 2 Tarapoto, periodo enero – agosto 2016 - Vasquez Cardenas, Denis (2016)
Objective: To demonstrate that transvaginal ultrasound cervicometry in pregnant women with preterm labor is a predictor of preterm labor at the MINSA II - 2 Tarapoto Hospital, January - august 2016. Methodology: An observational, analytical, retrospective, cross-sectional study of the diagnostic test was performed; between January and August 2016, the sample consisted of 81 clinical records of pregnant women with preterm birth threat who met the selection criteria. Sensitivity and specificity (as validity parameters), positive and negative predictive value (as safety parameters) and the ROC curve with its area under the curve (for diagnostic accuracy) were used to know the predictive diagnostic capacity. Results: Comparing cervicometry values between 15 and 30 mm, the cut-off point of 25 mm has the best sensitivity (88,9%) and specificity (81,5%), and the positive predictive value is 70,6 % and negative predictive value was 93,6%, being considered the optimal cut-off point for the study, in addition to presenting a statistically significant association (p = 0,001) for preterm labor OR = 35,20 (IC 95%: 8,83-140,30). Using the ROC curve, the area under the curve (AUC) was calculated to be 0,852 (IC95%: 0,760 - 0,944), demonstrating good diagnostic accuracy. Conclusion: Cervicometry has a high predictive value of preterm birth in pregnant women with preterm birth threat